KUALITAS PELAYANAN PUBLIK PADA SISTEM PELAYANAN SATU PINTU (PTSP) DI MAL PELAYANAN PUBLIK BARUGA PEMERINTAH DAERAH KOTA BAUBAU PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL - Rahmawati, Chendy; Sadat, Anwar; Muh. Askal Basir (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The purpose of this research is to assess the level of public service provided by the One-Stop Integrated Service (PTSP) system of the Baubau City Government.The methodology used is a qualitative descriptive approach, while the independent variable is the improvement of PTSP services assessed from community satisfaction and the quality of public services evaluated based on five indicators: tangible, reliability, responsiveness, assurance, and empathy.Six informants participated in the study through documentation, in-depth interviews, and direct observation to collect data, which was then evaluated using the Miles and Huberman model.The study findings indicate that, despite facing several challenges, including inadequate infrastructure and a lack of public awareness regarding procedures, the implementation of PTSP at the Baruga City Baubau Public Service Mall successfully improved service quality through process simplification and service time acceleration.